Improvement in Glycemic and Lipid Profiles in Type 2 Diabetics with a 90-Day Ketogenic Diet. (14th August 2019) - Walton, Chase M.; Perry, Katelyn; Hart, Richard H.; Berry, Steven L.; Bikman, Benjamin T.
Abstract : Because low-carbohydrate diets are effective strategies to improve insulin resistance, the hallmark of type 2 diabetes, the purpose of reporting these clinical cases was to reveal the meaningful changes observed in 90 days of low-carbohydrate (LC) ketogenic dietary intervention in female type 2 diabetics aged 18-45. Eleven women (BMI 36.3 kg/m 2 ) who were recently diagnosed with type 2 diabetes based on HbA1c over 6.5% (8.9%) volunteered to participate in an intensive dietary intervention to limit dietary carbohydrates to under 30 grams daily for 90 days. The main outcome was to determine the degree of change in HbA1c, while secondary outcomes included body weight, blood pressure, and blood lipids. The volunteers lost significant weight (85.7 ± 3.2 kg to76.7 ± 2.8 kg ) and lowered systolic (134.0 ± 1.6 to123.3 ± 1.1 mmHg ) and diastolic (89.9 ± 1.3 to82.6 ± 1.0 mmHg ) blood pressure. HbA1c dropped to 5.6%. Most blood lipids were significantly altered, including HDL cholesterol (43.1 ± 4.4 to52.3 ± 3.3 mg / dl ), triglycerides (177.0 ± 19.8 to92.1 ± 8.7 mg / dl ), and the TG : HDL ratio (4.7 ± 0.8 to1.9 ± 0.2 ). LDL cholesterol was not significantly different. AST and ALT, plasma markers of liver health, were reported for eight patients and revealed no significant changes. These findings indicate that a short-term intervention emphasizing protein and fat at the expense of dietary carbohydrate functionally reversed the diabetes diagnosis, as defined by HbA1c. Furthermore, the intervention lowered body weight and blood pressure, while eliciting favorable changes in blood lipids.